Analisis Strategi Pemasaran Kerajinan Rumah Tangga Anyaman Tikar Pandan Di Desa Pintu Padang Julu Kec. Siabu Kab. Mandailing Natal Sumatera Utara - Zuhro Amini Kamil Tanjung; Sri Ramadhani; Nuri Aslami (Universitas Labuhanbatu, 2023)
Handicraft mat woven pandanus is a product of the household industry in the village of Padang Julu door Siabu District Mandailing Natal North Sumatra which was bequeathed to the community as a processed product that is worth selling and art. This study aims to analyze the marketing strategy of household handicrafts woven pandanus mats in Pintu Padang Julu Village, Siabu District, Mandailing Natal regency, North Sumatra. Existing Data is the result of interviews, observations and documentation. The method used is qualitative descriptive approach with data reduction analysis model, data presentation and conclusion. The results showed that the strategy efforts that need to be done, namely 1) innovation style and shape, 2) expansion of marketing 3) the involvement of the younger generation, 4) the role of the village government and the Related Industry Department, this is to maintain the tradition and increase sales of woven pandanus leaf production.